2022
DOI: 10.54112/bcsrj.v2022i1.151
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Gene Actionfor the Selection of Superior Parents and Their Cross Combinationsfor Yield and Fiber Associated Attributes in American Cotton (Gossypium Hirsutum L.)

Abstract: Cotton is very important crop regarding the global trade. It is grown for its fiber and edible oil in Pakistan. It contributes 1.5 percent to GDP and 69 percent in foreign exchange. There is need to enhance the yield per unit area of cotton by developing high yielding and stress tolerant varieties. In breeding program the parents and their crosses are selected on the basis of their combining ability. Combining ability analysis is performed to identify the general and specific combiner for yield attributed trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Significant differences in the results indicated the genetic variation in the breeding material for yield and its related attributes. Similar results were also observed by (Fatima et al, 2022;Rehman et al, 2017;Imtiaz et al, 2022). So, these entries can be used for advance breeding programs.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Significant differences in the results indicated the genetic variation in the breeding material for yield and its related attributes. Similar results were also observed by (Fatima et al, 2022;Rehman et al, 2017;Imtiaz et al, 2022). So, these entries can be used for advance breeding programs.…”
Section: Resultssupporting
confidence: 87%
“…Combining ability analysis showed that mostly nonadditive type of gene action was governing in almost all characteristics (Fatima et al, 2022;Riaz et al, 2023). The GCA effects were significant in all traits except the monopodial branches.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In conclusion, the dawn of AI in agriculture marks an exciting era of innovation and progress. This review paper aims to explore the transformative potential of AI in agriculture, from its historical roots in predictive analysis to its current applications in precision farming and autonomous operations (Bhutta et al, 2023;Chaudhry et al, 2022;Fatima, Saeed, Ullah, et al, 2022). By analyzing the challenges and opportunities presented by Agricultural AI, this paper seeks to provide valuable insights for researchers, policymakers, and stakeholders working towards a sustainable and technologically advanced future in agriculture.…”
Section: Introductionmentioning
confidence: 99%